2020
DOI: 10.1124/mol.119.118190
|View full text |Cite
|
Sign up to set email alerts
|

LUF7244 plus Dofetilide Rescues Aberrant Kv11.1 Trafficking and Produces Functional IKv11.1

Abstract: Kv11.1 (hERG) channels play a critical role in repolarization of cardiomyocytes during the cardiac action potential (AP). Drug mediated Kv11.1 blockade results in AP prolongation, which poses an increased risk of sudden cardiac death.Many drugs, like pentamidine, interfere with normal Kv11.1 forward trafficking and thus reduce functional Kv11.1 channel densities. Although class III antiarrhythmics, e.g. dofetilide, rescue congenital and acquired forward trafficking defects, this is of little use due to their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…These drugs, however, are linked to drug-induced LQT ( Spector et al, 1996 ). Recently, it was found that the use of blockers and activators in combination could increase the functional expression of ERG1 channels ( Qile et al, 2019 , 2020 ), raising the possibility that these treatments could be used together to increase channel trafficking to the plasma membrane. Nevertheless, these maneuvers need to be studied further, because there is a high possibility that increasing the mutant ERG1 channels will result in additional problems, such as changes in gating or permeability, which could worsen LQT2 or their impact on neuronal function.…”
Section: Erg1 In Neuronal Physiology and Pathophysiologymentioning
confidence: 99%
“…These drugs, however, are linked to drug-induced LQT ( Spector et al, 1996 ). Recently, it was found that the use of blockers and activators in combination could increase the functional expression of ERG1 channels ( Qile et al, 2019 , 2020 ), raising the possibility that these treatments could be used together to increase channel trafficking to the plasma membrane. Nevertheless, these maneuvers need to be studied further, because there is a high possibility that increasing the mutant ERG1 channels will result in additional problems, such as changes in gating or permeability, which could worsen LQT2 or their impact on neuronal function.…”
Section: Erg1 In Neuronal Physiology and Pathophysiologymentioning
confidence: 99%
“…Further experimental investigations are, however, required to highlight the exact underlying mechanism. Another potential use of great clinical relevance for LUF7244 was highlighted in a recent study showing that pretreatment with a combination of LUF7244 and the high affinity inhibitor dofetilide, but not LUF7244 alone, enhanced the membrane expression of both WT and trafficking defective LQT2‐associated G601S hERG mutant 25 . Class III antiarrhythmic drugs such as dofetilide have been reported to rescue the expression of trafficking defective hERG channels but because of their I Kr / I hERG inhibitory properties, this has been of little clinical relevance 25 .…”
Section: Herg Agonist Drug Candidates For the Pharmacological Managem...mentioning
confidence: 99%
“…13,14 Another proposed target has been the selective activation of I Kr /I hERG by small activator drug molecules (hERG agonists) to increase repolarization reserve and counteract LQTS-associated triggered activity. This potential mechanism-based therapy has been investigated in several in vitro, in vivo, and in silico studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] for the management of the effects of both LQT2-associated mutations to hERG1 20,[24][25][26][27][28] and/or pharmacological blockade of the hERG channel. [16][17][18][19][20][21]23,31 Although promising drug candidates, there are still major drawbacks to their preclinical development and consequently none of these drug molecules have to date been trialled in clinical settings.…”
Section: Current Clinical Management Of Lqts and Use Of Herg Agonist ...mentioning
confidence: 99%
“…However, they could lead to abnormal shortening of the QT interval and increase the risk for deadly arrhythmias like ventricular fibrillation. Qile and colleagues (2020) determined whether the functional expression of Class 2 LQT2 Kv11.1 channels could be increased by culturing cells in I Kr blockers and the I Kr activator LUF7244 [58,59]. LUF7244 is an allosteric I Kr activator that counteracts I Kr blocker induced arrhythmias in dogs.…”
Section: Novel Therapeutic Approaches To Treat Lqt2mentioning
confidence: 99%